What is Saiva Siddhanta?: Tracing modern genealogies and historicising a classical canon - Klöber, Rafael (Journal of Hindu studies, 2017)
The philosophical tradition of Saiva Siddhanta is mainly prevalent in Tamil Nadu today. In spite of being seen as the fulfilment of Hinduism by its adherents, it has hardly received much scholarly attention in the studies on Indian religion. The few academic works that exist, however, have treated the tradition mainly as a philosophical topic and have hardly dealt with Saiva Siddhanta historically. Taking the established twenty-first century (Saivite and academic) commonsensical conceptualisations of the tradition as a starting point, this article will describe these widespread convictions through the examples of historical positioning and textual canon. I will argue that these conceptualisations can plausibly be traced to discourses of the mid-nineteenth century. As will be shown, this time is decisive for understanding present-day Saiva Siddhanta, since it was then that a conception of Saiva Siddhanta was established and sedimented in public and globally entangled discourse, still shaping today's assessment.
Gesehen am 05.12.2017